2020
DOI: 10.1002/ajb2.1475
|View full text |Cite
|
Sign up to set email alerts
|

Seed source regions drive fitness differences in invasive macrophytes

Abstract: Premise Worldwide, ecosystems are threatened by global changes, including biological invasions. Invasive species arriving in novel environments experience new climatic conditions that can affect their successful establishment. Determining the response of functional traits and fitness components of invasive populations from contrasting environments can provide a useful framework to assess species responses to climate change and the variability of these responses among source populations. Much research on macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
(93 reference statements)
2
2
0
Order By: Relevance
“…At 30 °C, the three populations originating from the Mediterranean region allocated more energy to biomass in general, and to the production of lateral shoots rather than to apical growth. These results are congruent with available literature (Rejmankova, 1992), and with a mesocosm experiment conducted in California (Gillard et al, 2020). Indeed, Gillard et al (2020) established that a higher climatic similarity in the source and invaded regions greatly assists the establishment and performance of L. peploides.…”
Section: Changes In Morphological and Physiological Traits With Increasing Temperaturesupporting
confidence: 91%
See 2 more Smart Citations
“…At 30 °C, the three populations originating from the Mediterranean region allocated more energy to biomass in general, and to the production of lateral shoots rather than to apical growth. These results are congruent with available literature (Rejmankova, 1992), and with a mesocosm experiment conducted in California (Gillard et al, 2020). Indeed, Gillard et al (2020) established that a higher climatic similarity in the source and invaded regions greatly assists the establishment and performance of L. peploides.…”
Section: Changes In Morphological and Physiological Traits With Increasing Temperaturesupporting
confidence: 91%
“…These results are congruent with available literature (Rejmankova, 1992), and with a mesocosm experiment conducted in California (Gillard et al, 2020). Indeed, Gillard et al (2020) established that a higher climatic similarity in the source and invaded regions greatly assists the establishment and performance of L. peploides. Overall, we found that Mediterranean populations of L. peploides performed significantly better at 30 °C than those from Oceanic populations.…”
Section: Changes In Morphological and Physiological Traits With Increasing Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…This and other reanalysis products, whose integrated frameworks mitigate issues of model and geographic bias ubiquitous to individual earth system models, remote sensing, and interpolated observational products (e.g. WorldClim), have enabled new capability for understanding the spread of IAS worldwide (Atala et al ., 2019; Gillard et al ., 2020).…”
Section: Spatial Environmental Datamentioning
confidence: 99%